Study of knowledge, attitude and practice of AYUSH doctors, evaluation of MHTs working in RBSK and client satisfaction - Parmar, Sachin; Bansal, S. B.; Raghunath, Deepa; Patidar, Ananad (International Journal Of Community Medicine And Public Health, 2017)
Background: Rashtriya Bal Swasthya Karyakram (RBSK) is newly launched programme under NRHM, under which screening of 6 month to 18 year children done by AYUSH doctors. The objective was to evaluate the infrastructure and staff available with mobile health teams (MHTs), knowledge, attitude and practice (KAP) of AYUSH doctors regarding 4Ds and client satisfaction for screening done by AYUSH doctors. Methods: Two blocks from each Indore and Ujjain district were randomly selected and observational check list made according to norms of RBSK was used for assessment of staffing pattern, availability of equipment’s with mobile health team. A pretested questionnaire is used to evaluate KAP of AYUSH doctors and client satisfaction. Results: According to the norms of Rashtriya Bal Swasthya Karyakram all the mobile health teams were deficient in terms of human resources and equipments. All the doctors under study were graduate in AYURVEDA, most of them were trained for RBSK and having good knowledge regarding the 4Ds, a significant difference was observed in their attitude and practice with regards to referrals and examination of children. Most of the beneficiaries were satisfied with the screening services. Conclusions: All Mobile Health Teams were deficient in paramedical staff and tool kit for screening where the used tools were replaced only once a year. And there is difference in attitude and practice of MHT doctors.